Determination of threshing and separation unit performance of rosemary (Rosmarinus officinalis) plants - Yilmaz, Deniz; Gökduman, Mehmet Emin (International Journal of Agricultural and Biological Engineering, 2021)
Rosemary (Rosmarinus officinalis L.) is an important perennial medicinal and aromatic plant belonging to the Lamiaceae family. Rosemary is widely produced in Turkey for its oil which can be extracted from the plants when flowers are in buds. In Turkey, a significant amount of domestic and foreign trade of rosemary is conducted. In 2018-2020, 2088 t of rosemary plants were imported, while in the same years 2077 t were exported. In this study, the performance indexes of a threshing and separating unit designed according to the physicomechanical properties of the rosemary were determined. The operating parameters of the machine were determined at three different moisture contents and adjusted according to the harvest moisture values. The threshing efficiency, work efficiency, power requirement, and specific energy consumption values of the threshing unit were determined, while separating efficiency, work efficiency and specific power consumption of separating unit of the developed system were determined. According to the study results, the threshing efficiency of the rosemary plant varied between 44.00% and 96.97%. Work efficiency of the thresher varied between 1.18 and 15.34 kg/h. Power requirements and specific energy consumption of the threshing unit were obtained as 0.19-1.05 kW and 0.02-0.37 kW·h/h, respectively. On the other hand, the separating efficiency of the separating unit for the rosemary plant varied between 44.27% and 85.24%. Maximum and minimum values of work efficiency were found as 0.75 kg/h and 5.52 kg/h. Specific power consumption of the unit ranged from 3.95 to 39.95 kW/kg. Keywords: rosemary, mechanization, threshing, separating, design, Turkey DOI: 10.25165/j.ijabe.20211406.6461 Citation: Yilmaz D, Gökduman M E. Determination of threshing and separation unit performance of rosemary (Rosmarinus officinalis) plants. Int J Agric & Biol Eng, 2021; 14(6): 237–243.